Islamisasi Ilmu Pengetahuan Menurut Pandangan Syed Muhammad Naquib Al-Attas Dan Implikasinya Terhadap Pengembangan PAI Di Perguruan Tinggi Umum - Muhammad Sayyidul Abrori; Muhammad Nurkholis (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Nurul Huda, 2019)
This abstract contains aboutthe Islamic concept of science according to al-Attas that the biggest challenge facing Muslims isthe challenge of knowledge spread throughout the Islamic world by Western civilization.Islamization of knowledge means Islamizing or purifying Western product science which has been developed and used as a reference in the development discourseIslamic education system in order to obtain a